THE ROLE OF ENGINEERING GRAPHICS IN THE TRAINING OF STUDENTS IN MECHANICAL SPECIALTIES - Василишин, Віталій (SWorldJournal, 2025)
Engineering graphics is a fundamental discipline in the system of technical education. It plays a key role in the formation of professional competence of students of mechanical specialties, as it provides basic skills of spatial representation, technical